Thermographic scrotal pattern in sound for breeding zebu bulls extensively managed in tropical Costa Rica - Chacón-Obando, A. (2016)
Infrared thermography (IR) is relatively a novel proce- dure in animal andrology for studying bull’s scrotal thermal pattern. The accuracy of this technique lies onto camera’s performance and operator skills, and although the high cost of the equipment is still a constraint for its broad use, it could assist on diagnosis and prognosis the sire’s potential fertility, since bulls with a disrupted testicular thermoregu- lation are linked with impaired semen quality. This report aims to outline the thermal scrotal pattern in sound for breeding Brahman sires, in order to reference these values when using IR for assisting during bull’s breeding sound- ness examination.